Impact of Anthropogenic Pollution on the Plant Species Diversity and Composition Along the Riparian Ecotones of Goa's Sal and Zuari Rivers - Moses Musisi; Celly Quadros; Krishnan Sellappan (Plant-Environment Interactions)
ABSTRACT Anthropogenic pressures are increasingly constraining the health of riparian ecosystems by exposing their remnant vegetation to edge effects. Despite being at the land–water interface, conservation efforts have often overlooked how water pollution may indirectly exacerbate the broader impacts of anthropogenic pressures on riparian vegetation along riparian ecotones. This study therefore examined the impacts of anthropogenic pollution on plant species diversity and composition in riparian ecosystems. Transect and Quadrat methods were used to collect vegetation data. We also measured the physicochemical properties of the water samples. We used partial redundancy analysis (RDA), generalized linear models (GLMs), analysis of variance (ANOVA), and Tukey's HSD test for data analysis using R software version 4.3.2. The study identified 126 plant species from 45 families, with the Shannon–Wiener diversity index ranging from 2.06 to 3.10. Anthropogenic disturbances were generally at the alpha eu‐hemerobic level, characterized by strong human impacts. Redundancy analysis showed that the nature of human activities, hemeroby, and turbidity were the dominant explanatory factors affecting plant species composition. GLM regression revealed that anthropogenic disturbances (hemeroby) had a significant negative impact on riparian plant species diversity mediated by water pollution. The findings indicate that anthropogenic disturbances coupled with their detrimental effects on water quality lead to a decrease in plant species richness and the dominance of a select few plant species. This will ultimately lead to a decline in the overall plant species diversity. Our findings show that anthropogenic disturbances negatively impact plant species diversity and composition through altering the water quality and habitat degradation. The findings therefore highlight the critical need for stakeholders to prioritize sustainable practices that mitigate water pollution and reduce direct human disturbances. This will safeguard biodiversity and ecosystem functionality in riparian zones, thus ensuring the long‐term stability of environmental services that benefit both nature and human communities.